Accounting for self-selection bias in assessing impacts of agricultural innovations : the case of farmer support programs in the Eastern Cape - Mungatana, Eric D. (University of Pretoria, 2022)
Mini Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2021.